On the need to unify initiatives for an ethical use of Artificial Intelligence - Nodals García, Carlos Lázaro (2020)
The objective of the work is to review, expose and understand the need to unify initiatives for an ethical use of Artificial Intelligence (AI). It exposes the relationship between science, ethics, society and the behavior of the science professional. Starting from the basic approaches of this technology, areas of proven benefits are described. In the methodology, consulting the databases Dialnet and Scielo, a systematic review was made of books, scientific articles, reports and declarations of parliaments, government agencies and international forums, as well as articles by specialists on the subject. The abstracts and full articles, in Spanish and English, were reviewed, considering those that dealt with the viable unification of all initiatives aimed at the ethical use of AI. The results show the risks of its uncritical and unethical implementation, the implications of the development of applications that incorporate Artificial Intelligence, for society and people in their private lives. There is talk of awareness by governments and citizens of the risks of this technology, and the urgency of unifying in a single model, its ethical, safe and transparent use. The conclusions show that a consensus prevails in the consulted literature on the need to unify the initiatives for their ethical and verifiable use, which shows an awareness of the potential risks of their development without a consensual control. But enthusiasm for the benefits of this technology prevails, which is an obstacle to achieving it.